Gastrointestinal basidiobolomycosis – A rare fungal infection: Challenging to diagnose yet treatable – Case report and literature review - Saeed Mirmoosavi; Mohammadreza Salehi; Reza Fatahi; Amanuel Godana Arero; Hasti Kamali Sarvestani; Farid Azmoudeh-Ardalan; Faeze Salahshour; Masoomeh Safaei; Sara Ghaderkhani; Foroogh Alborzi Avanaki (IDCases, 2023)
Gastrointestinal Basidiobolomycosis is a rare manifestation of Basidiobolus ranarum infection. In this report, we present two cases of gastrointestinal Basidiobolomycosis. The first patient presented with obstructive symptoms, fever, and weight loss. The diagnosis of Basidiobolomycosis was not made until after surgery, when Liposomal amphotericin-B combined with itraconazole were administered, leading to the resolution of laboratory markers of inflammation and patient's symptoms. The second case involves a young woman who presented with hematochezia, perianal induration, and abdominal pain. The patient had previously been diagnosed with Crohn's disease and treated accordingly, but her symptoms did not improve. Due to the endemicity of tuberculosis in Iran, the patient was treated for TB but still showed no improvement. However, a perianal biopsy sample revealed the Splendore Hoeppli phenomenon and fungal elements in GMS staining, leading to the diagnosis of gastrointestinal Basidiobolomycosis. Treatment with itraconazole and co-trimoxazole led to a significant improvement in symptoms and laboratory indices after one week, including the resolution of perianal induration. The key takeaway from this report is the importance of considering rare infections in the differential diagnosis of gastrointestinal conditions such as IBD and GI obstruction.